COMBINATION BENSON RELAXATION AND MURROTAL ALQURAN TO DECREASE ANXIETY, STRESS, AND DEPRESSION HEMODIALYSIS PATIENTS: AN EXPERIMENTAL STUDY - Riska Rohmawati; Ratna Yunita Sari; Imamatul Faizah; Siti Nur Hasina (Nurse and Health)
Background: Anxiety, stress and depression in hemodialysis patients often occur due to changes in lifestyle and boredom undergoing therapy. Data from the hospital 63.9% of hemodialysis clients experienced anxiety, 51.7% experienced stress, and 60.5% experienced depression.